Heterologous Covid-19 vaccines intervention effect on reactogenicity - Najeeb, Wajeha; Waheed, Palvasha; Khadim, Rehana (Journal of the Pakistan Medical Association, 2023)
To determine the change in the occurrence of short-term vaccine reactions on the use of heterologous Covid-19 booster, a single centre short-term study of two months duration was conducted. It was designed as an interventional study with registered clinical trial number # SLCTR/2022/008. It was conducted on medical students and faculty of a National university of medical sciences, Rawalpindi affiliated public sector medical college. A total of 348 individuals were administered with Ad5-nCoV vaccine and 101 with mRNA-1273 vaccine. They all had been previously vaccinated with two doses of BBIBP-CorV. BBIBP-CorV reactogenicity was considered a control group. Vaccine reactions, including pain and redness at the injection site, fever, no observed reactions at all, myalgia, feeling cold, dizziness, paraesthesia in the arm, light-headedness, had a significant change in their frequencies in comparison to homologous vaccine (BBIBP-CorV) reactogenicity. —Continue